How stakeholder participation can contribute to systematic reviews of complex interventions. Issue 2 (16th October 2015) - Harris, J; Croot, L; Thompson, J; Springett, J
Abstract : Although patient and public involvement in research is a requirement for research funding in many countries, the knowledge base for how to effectively involve people—and evidence of the effectiveness of involvement—is weak. This article describes how methods used in participatory health research were used to involve patients, clients, providers and community health workers across all stages of a realist review. Sustained involvement enabled better identification of the components of the complex intervention of community-based peer support. It also challenged assumptions of how peer support is constructed, leading the review team to question whether the process of designing and implementing interventions has more influence on effectiveness than previously recognised in empirical studies. We conclude with a discussion on when sustained involvement should be used, and the challenges of incorporating it into the traditional researcher-led approach to systematic reviews.